New copper(II) complexes containing tryptophan based Schiff bases as promising antiproliferative agents on breast cancer cells - Gultekin, Busra; Ozbagci, Duygu Inci; Aydin, Ipek; Aydin, Rahmiye; Ari, Ferda; Zorlu, Yunus (Elsevier, 2024)
Three new copper(II) complexes, [Cu(5-ClSal-Trp)(H2O)2] (1), [Cu(5-ClSal-Trp)(phen)] & sdot;C2H5OH (2) and [Cu (3,5-ClSal-Trp)(phen)] (3) (5-ClSal-Trp: Schiff base derived from 5-chlorosalicylaldehyde and L-tryptophan, 3,5-ClSal-Trp: Schiff base derived from 3,5-dichlorosalicylaldehyde and L-tryptophan, phen: 1,10-phenanthroline), have been synthesized and characterized by electronic absorption spectroscopy, CHN analysis, FTIR, ESI-MS and XRD techniques. Interaction of the complexes 1-3 with biomolecules {calf thymus DNA (CT-DNA) and bovine serum albumin (BSA)} has been investigated by electronic absorption and fluorescence spectroscopy. The results show that the complexes 1-3 can bind to CT-DNA via a moderate intercalation mode. Moreover, the fluorescence quenching mechanism between the complexes 1-3 and BSA is a static quenching process. Radical scavenging activity studies reveal that the complexes 1-3 show a moderate activity. Antiproliferative effects of the complexes 1-3 on both breast cancer cells (MCF-7 and MDA-MB-231) and healthy breast epithelial cells (MCF-10A) were also investigated using the Sulforhodamine B (SRB) viability assay. The results demonstrated that the complexes 1-3 exhibited a more pronounced cytotoxic effect on cancer cells compared to normal breast epithelial cells. Among the complexes, the best cytotoxic activity was obtained for the complex 3 against both human breast cancer cell lines. Further analysis indicated that the complex 3 induced apoptosis, as evidenced by fluorescent staining, positive Annexin-V-FITC staining, and the involvement of caspase. Subsequent to the administration of the complex 3, an evaluation of intracellular reactive oxygen species (ROS) generation was conducted through the utilization of dihydroethidium (DHE) fluorescent staining.
Keywords: Cu(II) complexes; Schiff base; Tryptophan; DNA/BSA interactions; Antiproliferative activity; Apoptosis